Quantifying the potential causes of Neanderthal extinction: Abrupt climate change versus competition and interbreeding. (15th June 2020) - Timmermann, Axel
Abstract: Anatomically Modern Humans are the sole survivor of a group of hominins that inhabited our planet during the last ice age and that included, among others, Homo neanderthalensis, Homo denisova, and Homo erectus . Whether previous hominin extinctions were triggered by external factors, such as abrupt climate change, volcanic eruptions or whether competition and interbreeding played major roles in their demise still remains unresolved. Here I present a spatially resolved numerical hominin dispersal model (HDM) with empirically constrained key parameters that simulates the migration and interaction of Anatomically Modern Humans and Neanderthals in the rapidly varying climatic environment of the last ice age. The model simulations document that rapid temperature and vegetation changes associated with Dansgaard-Oeschger events were not major drivers of global Neanderthal extinction between 50 and 35 thousand years ago, but played important roles regionally, in particular over northern Europe. According to a series of parameter sensitivity experiments conducted with the HDM, a realistic extinction of the Neanderthal population can only be simulated when Homo sapiens is chosen to be considerably more effective in exploiting scarce glacial food resources as compared to Neanderthals. Highlights: New model to study hominin interactions in time-varying climate environment. Neanderthals experienced rapid population decline due to competitive exclusion. Interbreeding only minor contributor to Neanderthal extinction. Abrupt Climate Change not major cause for demise of Neanderthals.